"Minimal" holoprosencephaly in a 14q deletion syndrome patient. Issue 12 (14th November 2017) - Della Giustina, Elvio; Iodice, Alessandro; Spagnoli, Carlotta; Giovannini, Simona; Frattini, Daniele; Fusco, Carlo; Gobbi, Giuseppe; Zollino, Marcella; Neri, Giovanni
Abstract : We report on a patient with terminal deletion of the long arm of chromosome 14 displaying brain interhemispheric fusion limited to the midline anterior frontal cortex associated with hypoplastic corpus callosum and incomplete rotation of the left hippocampus in a clinical setting of motor and intellectual disability with poor language, and social behavior abnormalities with aggressiveness. Some possible correlations between clinical signs and symptoms and various aspects of the complex brain malformation are briefly discussed and compared with other known abnormalities of chromosome 14. The different neuropathology of the most common forms and the new forms of holoprosencephaly recently described is also discussed and leads us to suggest classifying the interhemispheric fusion of this case as a "minimal" form of holoprosencephaly. This appears to be the first description in a 14q deletion patient.